The Impact of Celiprolol in Vascular Ehlers–Danlos Syndrome: A Systematic Review of Current Evidence - Pandit Bagus Tri Saputra; Wynne Widiarti; Paulus Parholong Siahaan; Rendra Mahardhika Putra; Johanes Nugroho Eko Putranto; Raden Mohammad Budiarto; Nadya Luthfah; Chaq El Chaq Zamzam Multazam; Mario D’Oria; Firas Farisi Alkaff (Medical Sciences, 2025)
Objectives: Ehlers–Danlos syndrome (EDS) is a group of connective tissue disorders characterized by mutations affecting collagen and extracellular matrix proteins. Vascular EDS (vEDS) stands out for its severe prognosis due to the heightened risk of arterial and organ rupture which significantly increase mortality rates. Limited strategies for treating vEDS are prompting exploration for alternatives such as celiprolol, a cardioselective beta-blocker with potential to reduce vascular stress and improve collagen integrity. This review aims to evaluate current evidence on the impact of celiprolol in managing vEDS. Methods: A comprehensive literature search was conducted across scientific databases for studies comparing celiprolol with placebo or other treatments, focusing on relevant outcomes. Results: A total of 323 participants were included across studies published from 2010 to 2023, primarily conducted in European settings. Celiprolol administration, starting at 100 mg daily and titrated up to 400 mg, significantly reduced the incidence of major vascular events such as arterial dissections and ruptures. Most studies reported improved survival rates and fewer hospitalizations due to acute arterial events. Variations in treatment response and side effects such as dizziness and hypotension were noted across studies, occasionally leading to treatment. Conclusions: Celiprolol appears to be a promising treatment for reducing vascular events in vEDS patients, potentially improving quality of life and mitigating the substantial morbidity and mortality associated with vEDS. Future research should focus on refining treatment protocols, exploring mechanisms of action, and establishing comprehensive clinical guidelines to optimize patient outcomes.